The Effect of Sales Promotion and Trust on Purchase Decisions on the Lazada Marketplace: marketing Management - Lulu Suwaryu; Endang Taufiqurahman (Fakultas Bisnis, 2022)
ABSTRACT The purpose of this study is to determine the influence and trustworthiness of purchasing decisions on the Lazada marketplace. The method used in this research is to use verification with a quantitative approach. The sample used in this study was 400 of the total Lazada Indonesia e-commerce visitors. The sampling technique used is non- probability sampling with incidental sampling method. Analysis of the data used is using path analysis with partial and simultaneous hypotheses. The results of this study are that there is a partial influence between Sales Promotion (X1) on Purchase Decisions (Y). there is a partial influence between Trust (X2) on the Purchase Decision (Y) of the Lazada marketplace . There is a simultaneous influence between sales promotion (X1) and trust (X2) on purchasing decisions (Y) Lazada marketplace.